Identifying the unmet needs of individuals with Type 2 diabetes: an international web-based survey - Raposo, Joao Filipe (2021)
Aim: To identify and understand the main unmet needs of individuals with Type 2 diabetes (T2D). Materials & methods: An online survey was conducted in Brazil, China and Russia of individuals with recently diagnosed T2D. Results: The survey, involving 300 individuals with T2D, identified a need for more information regarding food/diet and for increased awareness of T2D symptoms. While most participants (94%) had experienced symptoms prior to their diagnosis, only 55% of symptomatic individuals sought medical attention. Conclusion: Novel strategies to increase awareness of diabetes should be developed and tested, and may enable earlier diagnosis and improve patients' quality of life.